Luxury Fashion Brands and Furniture Design: Investigating Strategic Associations - Codignola, Federica (European Scientific Journal, ESJ, 2018)
The recent phenomenon of the modest growth in the personal luxury goods market has created an urge to face difficulties through innovative brand and marketing communication strategies. This paper examines the potentialities of strategic associations between luxury fashion brands and furniture design. The research question to be here examined is whether synergies with furniture design can represent possible innovative strategic instruments useful to compete in the global sector of the luxury fashion industry. To do so, this paper firstly examines the congruencies and the existent associations between fashion and design. Secondly, it compares luxury fashion brands with the specific furniture design market in order to verify whether and how such inter-sectoral convergence may effectively produce fluxes of value. Results indicate that the association between luxury fashion brands and collectible furniture design in particular is the most fruitful. The value of luxury brands is enhanced and consumers are provided at the same time with innovative and creative luxury experiences.